Buto, Ägypten: Die Siedlungsgeschichte des Fundplatzes Buto (Tell el Fara’in) - Hartung, Ulrich (e-Forschungsberichte des DAI, 2023)
The recent work of the German Archaeological Institute Cairo at Tell el- Fara’in/Buto focussed on the investigations of Early Dynastic settlement remains. From the beginning of the 1st until the middle of the 2nd Dynasty, three major phases of construction can be distinguished which may mirror the development of a royal estate with economic and administrative functions. As the latest phase a palace-like building complex comprising a representative area, magazines, workshops and rooms of cultic and private purpose was built on top of the preceding conctructions.